2009
DOI: 10.5205/reuol.581-3802-1-rv.0304200927
|View full text |Cite
|
Sign up to set email alerts
|

Idosos com úlceras venosas atendidos nos níveis primário e terciário em Natal/RN: caracterização sociodemográfica, saúde e assistência

Abstract: Objective: to characterize assistance of 88 elderly with venous ulcers attended in the tertiary and primary levels of health service in Natal city. Methods: integrative and descriptive study, from quantitative approach, with retrospective data of patients with venous ulcers who were studied in two dissertations presented at the Post-Graduate Program in Nursing/UFRN and a search report of CNPQ. Data was carried out from 2005 to 2007 through structured interview, physical examination and observation of the excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Algunos estudios señalan el acceso a este profesional en Brasil, en un estudio sobre la asistencia a los ancianos con UV atendidos en los servicios de salud en los niveles primario y terciario de asistencia del SUS, en Natal/Brasil, hubo un bajo nivel (39,8%) de acceso a la consulta con el angiólogo, siendo 20,5% en nivel terciario y 19,3% en primario. El acompañamiento especializado, la continuidad al tratamiento y la realización de exámenes (p= < 0,001) fueron más frecuentes en nivel primario de atención a la salud con 27,3%, 43,2% e 53,4%, respectivamente (23) . No obstante, otro estudio realizado a nivel ambulatorial en la red municipal de salud de Goiânia/Brasil revela que entre los que disponían de atención del médico, 67,2% de los investigados referían seguimiento del tratamiento con angiólogo, 13,8% con médico general, 6,9% con dermatólogo, 5,2% con cirugía general y solo 1,7% con médico de la Estrategia Salud de la Familia (10) .…”
Section: Discusionesunclassified
“…Algunos estudios señalan el acceso a este profesional en Brasil, en un estudio sobre la asistencia a los ancianos con UV atendidos en los servicios de salud en los niveles primario y terciario de asistencia del SUS, en Natal/Brasil, hubo un bajo nivel (39,8%) de acceso a la consulta con el angiólogo, siendo 20,5% en nivel terciario y 19,3% en primario. El acompañamiento especializado, la continuidad al tratamiento y la realización de exámenes (p= < 0,001) fueron más frecuentes en nivel primario de atención a la salud con 27,3%, 43,2% e 53,4%, respectivamente (23) . No obstante, otro estudio realizado a nivel ambulatorial en la red municipal de salud de Goiânia/Brasil revela que entre los que disponían de atención del médico, 67,2% de los investigados referían seguimiento del tratamiento con angiólogo, 13,8% con médico general, 6,9% con dermatólogo, 5,2% con cirugía general y solo 1,7% con médico de la Estrategia Salud de la Familia (10) .…”
Section: Discusionesunclassified
“…11 Besides occupation, another factor to be considered in Harrison points out that there is evidence that low socioeconomic status negatively influences healthy behavior in the home environment, access to health services, health care and access to material resources. 13 Household income is an important aspect in the planning of actions, as it determines the living conditions of this population, often making it difficult to implement actions, prolonging treatment and chronicity of lesions.…”
mentioning
confidence: 99%
“…6 With regard to health characteristics, several studies have reported that healthy lifestyle habits, such as not smoking, sleeping at least six hours, having a balanced diet, do not drink alcohol and take control of underlying diseases and risk factors, contribute positively to the healing of venous ulcers. [10][11][13][14] Corroborating this study, research conducted in a referral hospital for treatment to people with VU identified risk factors such as family history of venous disease; history (proven or suspected) of DVT; prior venous surgery or other sources; activities for long periods of standing or sitting; pregnancy; diabetes; heart disease; chronic venous insufficiency; hypertension and stroke. 15 Margolis identified chronic diseases such as hypertension (38,9%), lung disease (16,7%) and diabetes mellitus (11,1%).…”
mentioning
confidence: 99%
See 2 more Smart Citations